EFEKTIVITAS PELAKSANAAN PEMBINAAN TERHADAP NARAPIDANA RESIDIVIS TINDAK PIDANA NARKOTIKA DI LEMBAGA PEMASYARAKATAN KELAS II B SUNGAILIAT KABUPATEN BANGKA PROVINSI KEPULAUAN BANGKA BELITUNG - Arifandi, Farros; Erdiansyah, Erdiansyah; Andrikasmi, Sukamariko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Correctional Institutions are institutions whose principle is that guidanceand protection is the final process of criminal justice which imposes imprisonmenton convicts. It is hoped that this training will be an effective way for prisoners tolearn that the actions they have committed are wrong and deviant, and so thatthey do not repeat these crimes.This type of research can be classified as a type of sociological (empirical)legal research, because in this research the author directly conducts research atthe location or place being studied in order to provide a complete and clearpicture of the problem being studied. This research was conducted at the Class IIB Sungailiat Correctional Institution, Bangka Regency, Bangka BelitungProvince.The conclusions that can be obtained from the research results are: First,in Class II B Sungailiat Prison, the implementation of guidance for narcoticsprisoners has not been carried out effectively because only a few forms ofprograms have been carried out and this is supported by the number of narcoticscases which has increased every year so that there are more and more prisoners.Second, the obstacles faced by the Class II B Sungailiat Penitentiary in providingguidance are excess prison capacity; Lack of correctional officers; Developmentprogram for prisoners with different cases; factors from the prisoner's family; Theefforts taken by correctional officers or coaches to overcome obstacles orobstacles that arise in the coaching process are utilizing and maximizing existingprograms and officersKeywords: Development, Recidivism, Narcotics Crimes, Correctionalinstitution.